Red and blue light treatments of ripening bilberry fruits reveal differences in signalling through abscisic acid‐regulated anthocyanin biosynthesis. (12th August 2021) - Samkumar, Amos; Jones, Dan; Karppinen, Katja; Dare, Andrew P.; Sipari, Nina; Espley, Richard V.; Martinussen, Inger; Jaakola, Laura
Abstract: The biosynthesis of anthocyanins has been shown to be influenced by light quality. However, the molecular mechanisms underlying the light‐mediated regulation of fruit anthocyanin biosynthesis are not well understood. In this study, we analysed the effects of supplemental red and blue light on the anthocyanin biosynthesis in non‐climacteric bilberry ( Vaccinium myrtillus L.). After 6 days of continuous irradiation during ripening, both red and blue light elevated concentration of anthocyanins, up to 12‐ and 4‐folds, respectively, compared to the control. Transcriptomic analysis of ripening berries showed that both light treatments up‐regulated all the major anthocyanin structural genes, the key regulatory MYB transcription factors and abscisic acid (ABA) biosynthetic genes. However, higher induction of specific genes of anthocyanin and delphinidin biosynthesis alongside ABA signal perception and metabolism were found in red light. The difference in red and blue light signalling was found in 9‐ cis ‐epoxycarotenoid dioxygenase ( NCED ), ABA receptor pyrabactin resistance‐like ( PYL ) and catabolic ABA‐8'hydroxylase gene expression. Red light also up‐regulated expression of soluble N ‐ethylmaleimide‐sensitive factor attachment protein receptor (SNARE) domain transporters, which may indicate involvement of these proteins in vesicular trafficking of anthocyanins during fruit ripening. Our results suggest differential signal transduction and transport mechanisms between red and blue light in ABA‐regulated anthocyanin and delphinidin biosynthesis during bilberry fruit ripening. Abstract : Both red and blue light promoted anthocyanin biosynthesis in non‐climacteric bilberry fruit, regulated by abscisic acid metabolism. The key difference was detected in genes involved in abscisic acid (ABA) metabolism and signalling. Red light induced high accumulation of delphinidins towards end of berry ripening.